2019
DOI: 10.1039/c9pp00084d
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of photokinetics of 2’-ethylhexyl-4-methoxycinnamate in sunscreens

Abstract: 2′-Ethylhexyl-4-Methoxycinnamate (EHMC), also designated as octinoxate, is one of the most employed UVB absorbers in sunscreens for the protection of human skin against solar UV-radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Therefore, OMC and AVO were not considered photostable in formulations without photostabilizers (F1 and F1 RP), which are in agreement with the reports from literature (10,14,39,41) since they are known as photounstable UV‐filters that must be formulated with photostabilizers to produce stable sunscreen formulations. In addition, OMC and AVO have been studied regarding their mechanism of photodegradation and photoproducts using both diluted solutions and formulations.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, OMC and AVO were not considered photostable in formulations without photostabilizers (F1 and F1 RP), which are in agreement with the reports from literature (10,14,39,41) since they are known as photounstable UV‐filters that must be formulated with photostabilizers to produce stable sunscreen formulations. In addition, OMC and AVO have been studied regarding their mechanism of photodegradation and photoproducts using both diluted solutions and formulations.…”
Section: Resultssupporting
confidence: 82%
“…In a previous study, in ethanolic solution OMC showed no degradation after irradiation, but in the irradiated formulations OMC was significantly degraded (47). Thus, in diluted solutions (µM) the photoinstability of OMC might be related predominantly to the unimolecular photoisomerization trans/cis , but at higher concentrations in cosmetic formulations the concentration‐dependent bimolecular [2 + 2]‐cycloaddition can be detected (14,47). Meanwhile, it is well‐known that the photodegradation of AVO is induced by the keto‐enol tautomerization, followed by photodegradation reactions via triplet state leading to the loss of its effectiveness (10,48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now a days, a number of different UV absorbing molecules nd their use in commercial sunscreens [19][20][21]. There are 27 registered compounds, which are used as UV-lter in Europe as sunscreens [8].…”
Section: Introductionmentioning
confidence: 99%
“…Protection against sunlight supports to avert skin damage from unnecessary and extended contact to the sunlight. Excessive exposure to the sunlight can perform a major role in degenerative variations in the skin like photoaging and skin cancer [7][8][9][10][11][12]. It has been proved that ultraviolet (UV) radiations cause erythema solare [13].…”
Section: Introductionmentioning
confidence: 99%